STABILITY INDICATING RP-HPLC METHOD FOR THE ESTIMATION OF MILNACIPRAN HYDROCHLORIDE IN BULK AND ITS PHARMACEUTICAL DOSAGE FORM - SARAVANAN, G.; Yunoos, MD.; KUMAR, P. PRADEEP; Naveen Kumar, A. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To develop and validate a stability indicating reverse phase high performance liquid chromatographic method for the determination of Milnacipran hydrochloride in bulk and its pharmaceutical dosage form. Methods: The estimation was carried out on Agilent 1200 HPLC model equipped with UV detector using Kromasil C18 (100 × 4.6 mm, 5 µ particle size) column with potassium phosphate buffer (pH 3.3) and methanol (55:45, V/V) as mobile phase at a flow rate of 1.0 ml/min with UV detection at 220 nm. Results: The retention time was found to be 3.56 min and the proposed method was linear in the concentration range of 25-150 µg/ml (r2 = 0.999) with regression equation y = 25917x - 19637. The forced degradation studies were performed by using hydrochloric acid (0.1 N HCl), sodium hydroxide (0.1 N NaOH), hydrogen peroxide (10 percent H2O2), thermal and UV radiation. The results shown that Milnacipran hydrochloride was resistant to acidic, alkaline, oxidative, thermal and UV degradation. Conclusion: The developed method was validated as per ICH guidelines and can successfully be applied for the routine estimation of Milnacipran hydrochloride in bulk and formulations. Keywords: HPLC, Milnacipran hydrochloride, ICH, Kromasil C18